Microbiological and Antibiotic Profile of Broncho-Alveolar Lavage Aspirate in Mechanically Ventilated Patients in a Tertiary Care Hospital - Yadav, Rajesh; Thapa, Ajay Singh; Basnet, Rajan (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: VAP increases the patient stay in the ICU and indirectly increases the cost of patient management. Based on the time of onset of VAP, it can be divided into two types. Early-onset VAP occurs during the first four days of mechanical ventilation and is usually caused by antibiotic sensitive bacteria. Late-onset VAP develops five or more days after initiation of MV and is caused by multidrug-resistant (MDR) pathogens.5 Early diagnosis of VAP with appropriate antibiotic therapy can reduce the emergence of resistant organisms. Methods: This cross-sectional study was done in College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan after taking clearance from the institutional review committee. Study included all the patients who required mechanical ventilation for more than 72 hoursAll the included patients had their endotracheal tube aspirated using an ambu bronchoscope and sent to microbiology department for culture and sensitivity. The reports were collected after 72. Results: The most common organism grown during culture and gram staining were Acinetobacter Baumannii (81), followed by Klebsiella Peumoniae (44) than Pseudomonas Aeroginosa (32).. We observed a higher rate of culture positivity from the samples of male patients than those obtained from the female patients. Similar findings were observed by Morehead et al13and debjita debnath et al12 . In our study, gram-negative bacilli were the most commonly isolated pathogen from BAL which is similar to studies done by, debjita debnath, Fagon et al14 and Şimşek et al15. In our study, Acinetobacter Baumannii (81) was the most common followed by Klebsiella Peumoniae (44) than Pseudomonas Aeroginosa (32),first line of antibiotics in patients who were mechanically ventilated were piperacillin plus tazobactam, meropenem,cotrimoxazole, amikacin and gentamicin. The second line drugs were polymyxin B, colistimethate and tigecycline. Conclusions: Acinetobactor Baumanni is the most common causative organism of ventilator associated pneumonia. In most of the cases first line antibiotics ( meropenem, amikacin and clotrimoxazole) are sensitive. Among the second line antibiotics, Polymyxin B was found to be most effective.